KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS VII SMP NEGERI 9 PEKANBARU - FANI DEFRINA; Abdul Razak; Elmustian Rahman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study titled Essay Writing Ability Description Seventh Grade Students of SMP N 9 Pekanbaru. This study aims to determine the level of ability to write the essay description seventh grade students of SMP Negeri 9 Pekanbaru Academic Year 2016/2017. The method used is descriptive method. Data of this study was the result of tests kemapuan description essay writing class VII SMP Negeri 9 Pekanbaru consisting of nine classes with a population of 327 students and the sample size of 180 students. Results of research kemqampuan description essay writing class VII SMPN 9 Pekanbaru on aspects of compliance of the content with the title essay. Value - average at 86.11 with the first aspect of the precision aspect tinggi.Pada category title with a theme bouquet average value of 89.44 with ntinggi category. Then the third aspect of the precision of the use of language with an average value of 90.64 high category.